2013
DOI: 10.5194/angeo-31-503-2013
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Wave-Particle Interaction Analyzer for direct measurements of nonlinear wave-particle interactions

Abstract: In the upcoming JAXA/ERG satellite mission, Wave Particle Interaction Analyzer (WPIA) will be installed as an onboard software function. We study the statistical significance of the WPIA for measurement of the energy transfer process between energetic electrons and whistler-mode chorus emissions in the Earth's inner magnetosphere. The WPIA measures a relative phase angle between the wave vector E and velocity vector v of each electron and computes their inner product W, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 38 publications
1
51
0
Order By: Relevance
“…The fundamental concept of the WPIA is described by Fukuhara et al (2009) and Katoh et al (2013). The WPIA requires instantaneous-wave field vectors and velocity vectors of incoming plasma particles.…”
Section: Principle Of Wave-particle Interaction Analyzermentioning
confidence: 99%
See 1 more Smart Citation
“…The fundamental concept of the WPIA is described by Fukuhara et al (2009) and Katoh et al (2013). The WPIA requires instantaneous-wave field vectors and velocity vectors of incoming plasma particles.…”
Section: Principle Of Wave-particle Interaction Analyzermentioning
confidence: 99%
“…This improves the signal-to-noise ratio of the S-WPIA because the frequency variation changes the energy and pitch angle ranges of electrons, satisfying the cyclotron resonance condition. Katoh et al (2013) demonstrated the validity of the calculation method in the WPIA by conducting pseudocalculations of the WPIA using the data obtained by the particle simulations that represent the resonance between whistler-mode chorus waves and energetic electrons. The simulation was a one-dimensional (1D) electron-hybrid code with a dipole magnetic field near the magnetic equator.…”
Section: Computation Of Wmentioning
confidence: 99%
“…The WPIA measurement in the simulation is described in Katoh et al (2013), and we conduct the WPIA measurement in the same processing. The full-particle simulation code is used for the generation of whistler-mode chorus waves (Hikishima et al 2009a(Hikishima et al , 2009b(Hikishima et al , 2010).…”
Section: Pseudo-measurement Of Wpia In Simulationmentioning
confidence: 99%
“…By the WPIA, we can thereby identify the efficiency of the energy exchange through wave-particle interactions by selecting the range of the kinetic energy and pitch angle of electrons used in the computation of W int . The statistical significance of the obtained W int is evaluated by the standard deviation s W [3].…”
Section: Feasibility Of Swpiamentioning
confidence: 99%
“…So as to overcome the difficulty of the direct measurement of wave-particle interactions, we have proposed a new instrumentation "Wave-Particle Interaction Analyzer (WPIA)" [1][2][3]. Figure 1 represents the procedure of the Software-type WPIA (SWPIA) to be installed in the upcoming JAXA satellite mission ERG (Exploration of energization and Radiation in Geospace) as a software function running on the onboard CPU of the satellite.…”
Section: Introductionmentioning
confidence: 99%